Systemic Inflammation Associates With a Myeloid Inflamed Tumor Microenvironment in Primary Resected Colon Cancer—May Cold Tumors Simply Be Too Hot? - Køstner, Anne Helene; Nielsen, Patricia Switten; Georgsen, Jeanette Baehr; Parner, Erik Thorlund; Nielsen, Mette Bak; Kersten, Christian; Steiniche, Torben (Frontiers in Immunology, 2021)
Systemic inflammation measured by the acute phase protein CRP associates with poor outcome across cancer types. In contrast, local tumor-associated inflammation, primarily evaluated by T-lymphocytes, correlates with favorable prognosis. Yet, little is known whether these two responses are related or opposing processes and why elevated CRP in relation to cancer is detrimental for clinical outcome. As proof-of-concept we developed a platform combining multiplexed IHC and digital imaging enabling a virtual read-out of both lymphoid and myeloid immune markers and their spatial patterns in the primary tumors of resected stage II and III colon cancer (CC) patients with and without accompanying systemic inflammation. 21 patients with elevated CRP (>30 mg/L) and 15 patients with low CRP (<10 mg/L) were included in the analyses. Whole slides from the primary tumors were stained for markers of adaptive (CD8+, CD4+, foxp3 regulatory T cells, CD20+ B cells) and innate (CD68+ macrophages, CD66b+ neutrophils) immunity and the immune checkpoint molecule PD-L1. Associations between individual immune markers, preoperative CRP-values, mismatch repair-status (MMR) and risk of recurrence or death were assessed. Unsupervised hierarchical clustering was used to explore whether distinct immune phenotypes were present. Tumors from systemically inflamed patients (CRP >30 mg/L) displayed significantly more myeloid features in terms of higher densities of CD66b+neutrophils (p=0.001) and CD68+macrophages (p=0.04) and less lymphoid features (lower CD8 T cell, p=0.03, and foxp3 regulatory T cell densities, p=0.03) regardless of MMR-status. Additionally, systemically inflamed patients harbored lower mean distances between neutrophils and tumor cells within the TME. Intriguingly, microsatellite instable (MSI) tumor status correlated with systemic inflammation. However, using a combinatorial approach, we found that regardless of an adaptive composite score (compounded CD4+ and CD8+ T cells), a high innate score (CD66b+ neutrophils and CD68+ macrophages) associated significantly with elevated CRP. In conclusion, tumor-associated systemic inflammation correlated with a myeloid-dominated TME in a small cohort of resectable CC patients. Our data highlights the importance of a comprehensive immune classification of tumors including players of innate immunity and supports a role for CRP as an informative biomarker of the immune response taking place at the tumor site.